Measurement and error analysis of Cu film thickness with Ta barrier layer on wafer for CMP application - Qu, Zilian (2022)
Accurate thickness measurement of copper (Cu) film on silicon (Si)-based wafers is very important in the chemical mechanical polishing (CMP) process. For thickness measurement of Cu film, the eddy current method is widely adopted due to noncontact, high-efficiency, and high-accuracy characteristics. However, existing thickness measurements of Cu film ignore the effect of tantalum (Ta) barrier layer between Cu film and Si substrate, which makes the measurement result inaccurate. Therefore, it is necessary to investigate the effect of Ta barrier layer on thickness measurement of Cu film. In this article, an improved eddy current sensor system with a nanoscale resolution is proposed. It is based on the inductance-capacitance resonance principle and theoretical analysis is conducted. Several Si-based specimens with pure Cu film, pure Ta film, and Cu-Ta multilayer structure are prepared and measured. Experimental results show that there exists a balance thickness of Ta barrier layer as a threshold in Cu-Ta multilayer structure. When the thickness of Ta barrier layer is larger than the threshold, the measured thickness of Cu film increases with the increase of Ta barrier layer thickness. Conversely, the measured thickness of Cu film decreases when Ta barrier layer is thinner than the threshold. Then, a compensation method is presented, and the error of thickness measurement of Cu film is reduced to less than 6 nm.